Faktor-Faktor yang Berhubungan dengan Penerapan Teknologi Usaha Tani Padi Sawah di Desa Puosu Jaya Kecamatan Konda Kabupaten Konawe Selatan - Purnamasari, Nita; Hamzah, Awaluddin; Gafaruddin, Abdul (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2018)
The purpose of this research is to know the factors related to the application of technology on paddy field farming in Puosu Jaya Village Konda Subdistrict of South Konawe Regency. The population in this study were rice farmers who are in the Village Puosu Jaya Subdistrict Konda consisting of 16 people and sampling done by purposivesampling. Data collection techniques in this study are questionnaires and interviews.The variables observed in this study are independent variables witch include : age, education nuber of family dependens, farming experience, farming area, and intensity of agricultural extension followers. The dependent variable isthe application level of paddy farming technology. Thr results of this studyindicate that there is a relaptionship between age, education level, arable landarea, the number of family dependens and intensity of agricultural extention with the application of paddy farming technology. It can be seen by product moments correlation test with value (age = 0,0093, education = 0,758, farming experience = 0,802, total family member = 0,542, land area = 0,532, agricultural extention intensity = 0,595). Until it can be concluded that the relationship between the level of application of paddy farming technology related significantly whith age, educations level, farming land area, the number of dependents of family, and the participation of famers in agricultural extension activities. Famers are active in counseling activities and who have large land area tend to be higher in the application of technology of paddy farming.